E-056 Endovascular treatment of medically refractory cerebral vasospasm following aneurysmal subarachnoid hemorrhage. (16th November 2010) - Hetts, S; Jun, P; Ko, N; English, J; Dowd, C; Higashida, R; Halbach, V
Abstract : Background and purpose: Cerebral vasospasm (CV) following aneurysmal subarachnoid hemorrhage (SAH) is a significant cause of morbidity and mortality. We review our experiences using percutaneous transluminal angioplasty (PTA) and intra-arterial (IA) verapamil infusion for treating medically refractory cases. Materials and methods: Retrospective review of SAH patients admitted from July 2003 to January 2008. Results: Of 546 patients admitted with SAH, 231 patients (42%) developed symptomatic CV and 189 patients (35%) required endovascular therapy. A total of 346 endovascular sessions were performed consisting of a single angioplasty, 286 IA verapamil infusions and 59 combined therapies. PTA was performed on 151 vessel segments and IA verapamil infused in 720 vessel segments. IA verapamil doses ranged from 2.0 to 30.0 mg per vessel segment and 3.0 to 55.0 mg per treatment session. Repeat treatments were necessary in 182 patients (96%) for persistent, recurrent or worsening CV. There were six treatment related complications (1.7%) of which two (0.6%) resulted in clinical worsening. No deaths were attributable to endovascular therapy. At follow-up, 115 patients (61%) had a good outcome and 55 patients (29%) had a poor outcome. Sixteen patients died from causes related to SAH while three died from other medical complications. Conclusion: Endovascular treatments are an integral part of managing patients with medically refractory CV. In our experience, PTA and IA verapamil are safe with a very low complication rate but further studies are required to determine appropriate patient selection and treatment efficacy.